Susceptibility to eight common chemical insecticides in Helicoverpa zea populations from the southern United States - Bhavana Patla; Tiago Silva; Shucong Lin; Graham P. Head; Francis P.F. Reay-Jones; Xinzhi Ni; Lina Bernaola; Sebe Brown; Don Cook; James Villegas; Jeffrey A. Davis; Fangneng Huang (Crop Protection, 2026)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

A role for artificial night-time lighting in long-term changes in populations of 100 widespread macro-moths in UK and Ireland: a citizen-science study - John Fawcett Wilson; David Baker; Janet Cheney; Mike Cook; Martin Ellis; Roger Freestone; David Gardner; Graham Geen; Robin Hemming; Don Hodgers; Stephen Howarth; Ade Jupp; et al. (Journal of Insect Conservation, 2018)

A Framework for Quantitative Assessment of Impacts Related to Energy and Mineral Resource Development - Seth S. Haines; Jay E. Diffendorfer; Laurie Balistrieri; Byron Berger; Troy Cook; Don DeAngelis; Holly Doremus; Donald L. Gautier; Tanya Gallegos; Margot Gerritsen; Elisabeth Graffy; Sarah Hawkins; et al. (Natural Resources Research, 2014)

Phylogenetic analysis of actinobacterial populations associated with Antarctic Dry Valley mineral soils - Olubukola O. Babalola; Bronwyn M. Kirby; Marilize Le Roes‐Hill; Andrew E. Cook; S. Craig Cary; Stephanie G. Burton; Don A. Cowan (Environmental Microbiology, 2009)
Summary Despite the apparent severity of the environmental conditions in the McMurdo Dry Valleys, Eastern Antarctica, recent phylogenetic studies conducted on mineral soil samples have revealed the presence of a wide diversity of microorganisms, with actinobacteria representing one of the largest phylotypic groups. Previous metagenomic studies have shown that the majority of Antarctic actinobacterial populations are classified as ‘uncultured’. In this study, we assessed the diversity of actinobacteria in Antarctic cold desert soils by complementing traditional culture‐based techniques with a metagenomic study. Phylogenetic analysis of clones generated with actinobacterium‐ and streptomycete‐specific PCR primers revealed that the majority of the phylotypes were most closely related to uncultured Pseudonocardia and Nocardioides species. Phylotypes most closely related to a number of rarer actinobacteria genera, including Geodermatophilus , Modestobacter and Sporichthya , were also identified. While complementary culture‐dependent studies isolated a number of Nocardia and Pseudonocardia species, the majority of the cultured isolates (> 80%) were S treptomyces species – although phylotypes affiliated to the genus Streptomyces were detected at a low frequency in the metagenomic study. This study confirms that Antarctic Dry Valley desert soil harbours highly diverse actinobacterial communities and suggests that many of the phylotypes identified may represent novel, uncultured species.

Purification of ribulose 1,5-bisphosphate carboxylase/oxygenase and of carboxysomes from Thiobacillus thyasiris the putative symbiont of Thyasira flexuosa (Montagu) - Tom Lanaras; Catherine M. Cook; Ann P. Wood; Don P. Kelly; Geoffrey A. Codd (Archives of Microbiology, 1991)